Programma: 15 juli Chris Thomas; 16 juli Carl Cox & Per; 21 juli Banco de Gaia; 22 juli The Adolescents, NRA
Programma: 15 juli Chris Thomas; 16 juli Carl Cox & Per; 21 juli Banco de Gaia; 22 juli The Adolescents, NRA.